An Outsider Inside: Becoming a Scholar of Contemporary Paganism - Berger, Helen A. (The pomegranate, 2015)
This article explores how serendipity resulted in one sociologist becoming a scholar of a minority religion of which she is not a member. As one of the early scholars of contemporary Paganism, Berger describes both its transformation in the past thirty years and her contribution to that change. She argues that contemporary Paganism, with its lack of rigid structures and use of virtual space to create a "disorganized community" with a network of interactions, learning, and sharing is an excellent venue for studying many aspects of religion, culture, and political action in late modernity